"The Most Exotic was the Owner of the Pizzeria" - Exploring the Relationship between Subjective Diversity and Ethnic Identity. Issue 2 (3rd April 2023) - Svensson, Ylva; Syed, Moin
ABSTRACT: The aim of the present study was to examine how Swedish youth a) experience diversity and b) link those diversity experiences to their identities. Using a mixed-method approach, we coded written narratives for type of diversity experience, meaning-making, and analyzed qualitative differences due to the proximity of the setting and self-defined in- and outgroups. Out of 197 participants (age 15–29), 63 (31.5%) wrote about diversity in their narratives, and of those, 55 (87%) derived meaning about themselves or others. Qualitative differences were found between participants who self-identified with a majority, minority, or mixed ethnic identities. Youth who identified with a majority identity generally experienced being in the majority in the macro-setting while a lack of diversity in their micro-settings, and mainly derived meanings related to the ethnic identities of others. Youth who identified with minority or mixed ethnic identities, experienced being the minority in both micro- and macro-settings, and mainly derived meanings related to their own ethnic identity, such as enhanced identities or issues of belongingness. Results suggest that experiences of diversity trigger ethnic identity development, however, in a segregated society with unequal opportunities and power relations, those experiences and how they inform ethnic identity significantly vary significantly due to background.